Nano - Structured Hesperidin: Evaluation the Antioxidant Activities In Vitro - Ghassan M. Sulaiman (Journal of Global Pharma Technology, 2018)
Hesperidin from citrus peels is known to have anti-inflammatory, vaso-protective, hypo-lipidemic, anti-allergic, anti-carcinogenic and antioxidant actions. Current study was designed to evaluate the antioxidant capacity of hesperidin and hesperidin nanoparticles by using simple in vitro free radical scavenging system including, DPPH free radical-scavenging, hydrogen peroxide scavenging and Resazurin dye scavenging activities. Hesperidin nanoparticles showed strong scavenging effects against DPPH, hydrogen peroxide and Resazurin dye, and this effect was more potent than pure hesperidin. The scavenging activity of hesperidin nanoparticles was concentrations dependent, in the range of 100-400 µg mL-1showing a maximum activity of 80% at 400 µg mL-1in similar way to Vit.C which was used as positive control. In conclusion, this work displayed that hesperidin exhibited antioxidant activity and could be considered as a source of antioxidants from nature.Keywords: Hesperidin nanoparticles, Antioxidants, Resazurin, DPPH, Hydroxyl.